2022
DOI: 10.1021/acs.jafc.1c07153
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Strategies for LC–MS-Based Untargeted and Targeted Metabolomics Approaches Reveal the Entomological Origins of Honey

Abstract: A comprehensive liquid chromatography−mass spectrometry (LC−MS)-based metabolomics approach was developed to discriminate honey harvested from Apis mellifera ligustica Spinola (A. mellifera) and Apis cerana cerana Fabricius (A. cerana). Based on an untargeted strategy, ultrahigh-performance liquid chromatography electrospray ionization quadrupole orbitrap high-resolution mass spectrometry (UPLC Q-Orbitrap) was combined with chemometrics techniques to screen and identify tentative markers from A. mellifera and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…The identification of citrus flavonoids or authentic molecular markers in orange juices was achieved using data acquired by UHPLC Q-Orbitrap Full MS/ddMS 2 (TopN). One of the HRMS-metabolomics applications for food authentication is to convert nontarget findings to target methods by identifying markers of interest, ,, and the markers can be quantitated to determine an authentic product or indicate the presence of an adulterant …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of citrus flavonoids or authentic molecular markers in orange juices was achieved using data acquired by UHPLC Q-Orbitrap Full MS/ddMS 2 (TopN). One of the HRMS-metabolomics applications for food authentication is to convert nontarget findings to target methods by identifying markers of interest, ,, and the markers can be quantitated to determine an authentic product or indicate the presence of an adulterant …”
Section: Resultsmentioning
confidence: 99%
“…The identification of citrus flavonoids or authentic molecular markers in orange juices was achieved using data acquired by UHPLC Q-Orbitrap Full MS/ddMS 2 (TopN). One of the HRMS-metabolomics applications for food authentication is to convert nontarget findings to target methods by identifying markers of interest, 13,25,26 and the markers can be quantitated to determine an authentic product or indicate the presence of an adulterant. 9 When setting a result filter with a criterion that the amount of compounds was four times higher in NFCs than that in FCs using Log 2 Fold Change ≥2 in Compound Discoverer, 64 compounds were identified in the compound table (data not shown).…”
Section: Molecular Markers In Orangementioning
confidence: 99%
“…The second focus of the current study was to explore how the three extraction methods affected profiling for identification of molecular markers. One HRMS-based nontarget metabolomics application for food authenticity involves converting results from a nontarget study to a target method by identifying markers of interest. , In this way, the markers could be quantitated to determine their amounts to either identify an authentic product or indicate the presence of an adulterant, and the interpretation of the results from a target method would be straightforward. Differential analysis, hierarchical cluster analysis, and result filters in Compound Discoverer were used to find and identify molecular markers.…”
Section: Resultsmentioning
confidence: 99%
“…mellifera, which is used for the effective identification of ACH and AMH . Wang et al used metabolomics methods employing headspace gas chromatography-ion mobility spectrometry (HS-GC-IMS), liquid chromatography–mass spectrometry (LC–MS), and headspace solid-phase coupled with microextraction gas chromatography–mass spectrometry (HS-SPME-GC–MS) to identify ACH and AMH. , Zhang et al established the identification methods of ACH and AMH describing the major royal jelly protein profiles, major royal jelly protein 2 (MRJP2) gene, and hydrocarbon components. , Lee et al used sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) to determine the insect origin of honey produced by native Korean bees and European bees . It is evident from the above studies that bee-derived components are effective indicators for identifying ACH and AMH; however, it has been reported that the chemical composition of honey depends mainly on its plant origin, especially phenolic compounds, which in turn depends largely on the geographical origin of the honey .…”
Section: Introductionmentioning
confidence: 99%